KISAH ZAID BIN HARITSAH DALAM PERANG MUT’AH - As’alul Afiyah (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2021)
Abstract: This article examined a number of issues related to the history of Zaid bin Haritsah and his role in the Mu'tah War. This study used historical methods through heuristics, verification, interpretation, and historiography. The data were obtained from various selected sources. Here the leadership theory according to Max Weber and the role theory according to Soerjono Soekanto were applied to explain the leadership role of Zaid in Islam. It concluded that (1) Zaid bin Harithah was born about 47 years before the hijrah and died as a martyr in the Mu'tah at the age of 55 years; (2) Zaid played roles in the Islamic preaching as well as a public leadership in Medina and actively involved in several wars; (3) in the Mu'tah War Zaid bin Harithah was elected as a commander along with Ja'far bin Abi Talib, and Abdullah bin Rawahah. This mission was his last devotion to Islam before killed in the battle. Keywords: Zaid bin Haritsah, Friends, roles, Mu'tah war, struggle